2019
DOI: 10.9734/jeai/2019/v41i530417
|View full text |Cite
|
Sign up to set email alerts
|

Cause and Effect Estimates on Corn Yield as a Function of Tractor Planting Speed

Abstract: The objective of this work was to explain the cause and effect estimates on corn yield as a function of planting speed. The study was conducted from January 21 to June 15, 2019, at Fazenda Invernadinha, rural area of ​​the municipality of Mineiros, GO, Brazil. The experimental design consisted of randomized blocks, corresponding to five tractor planting velocities (4, 6, 8, 10 and 12 km h-1), in 4 replicates, where each plot consisted of 8 300 m long lines spaced at each 0.9 m, for a population of 60.000 plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 3 publications
1
2
0
1
Order By: Relevance
“…Although the correlation analysis is important to understand the interrelationships between the characteristics, high values do not necessarily imply a cause and effect relationship. As well as, in this work where high correlations can be observed, corroborating with Melo et al (2019) when working with corn genotypes, as well as in Ferreira et al (2019a) and Ferreira et al (2019b). In the analysis of simple correlation, the formation of 2 significant pairs was observed for the spacing between lines of 0.45 m, being the YI x TGM (0.85) and NGR x NGE (0.85) (Figure 3 E45), as well as, TGM x YI (0.85), NGR x NGE (0.76) and NGE x NRE (0.66) for lines spaced at 0.90 m (Figure 3 E90).…”
Section: Genotypesupporting
confidence: 90%
“…Although the correlation analysis is important to understand the interrelationships between the characteristics, high values do not necessarily imply a cause and effect relationship. As well as, in this work where high correlations can be observed, corroborating with Melo et al (2019) when working with corn genotypes, as well as in Ferreira et al (2019a) and Ferreira et al (2019b). In the analysis of simple correlation, the formation of 2 significant pairs was observed for the spacing between lines of 0.45 m, being the YI x TGM (0.85) and NGR x NGE (0.85) (Figure 3 E45), as well as, TGM x YI (0.85), NGR x NGE (0.76) and NGE x NRE (0.66) for lines spaced at 0.90 m (Figure 3 E90).…”
Section: Genotypesupporting
confidence: 90%
“…In the analysis of principal components, the sum of the pairs was of the order of 76% of explanation of the total variation of the data (Figure 3). The analysis of canonical variables is still scarce in the literature, and works with good responses in the Cerrado are reported, such as Ferreira et al (2019a) and Ferreira et al (2019b). The TMG1180 genotype at all concentrations showed similarities for the characters In the direct and indirect effects of the explanatory characters on those of production, the regression coefficients (r) were adjusted and validated by the probabilities (p) of both canonical pairs.…”
Section: Resultsmentioning
confidence: 99%
“…In breeding programs, generally, in addition to aiming to improve a main character, we also seek to maintain or improve the expression of other characters simultaneously. In soybeans, studies on correlations involving their characters with different focuses are reported by Bárbaro et al (2007), Sha et al (2016), Zhang et al (2016, Kong et al (2019), Ferreira et al (2019a), Ferreira et al (2019b and Kurt et al (2020), however, there are no references to the correlations that describe their magnitudes with phosphate fertilization.…”
Section: Introductionmentioning
confidence: 99%
“…A semeadura de milho é uma das práticas de manejo que mais afetam a produtividade (FERREIRA et al 2019). Como os custos de produção têm aumentado nos últimos anos, é necessário que os produtores busquem o arranjo espacial (taxa de semeadura x espaçamento entre linhas) que maximize a produtividade.…”
Section: Introductionunclassified